Implementasi PAI dalam Penguatan Profil Pelajar Pancasila Melalui Student Festival di MTs Darul Ulum Pasuruan - Lailatul Muarofah; M. Jamhuri; Achmat Mubarok; Muhammad Nur Hadi (Al-Abshor : Jurnal Pendidikan Agama Islam, 2025)
This study aims to describe the implementation of Islamic Religious Education (PAI) in strengthening the Pancasila Student Profile through the Student Festival at MTs Darul Ulum Pasuruan. The background of this research stems from the important role of PAI in shaping the character of students who are not only intellectually intelligent, but also devout, pious, and have noble morals. In line with national education policy, the Pancasila Student Profile serves as a guideline for cultivating a generation that is religious, creative, independent, critical, collaborative, and able to appreciate diversity. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The research subjects consisted of the madrasah principal, PAI teachers, the activity committee, and students. Data analysis was conducted using the Miles and Huberman interactive model, while data validity was achieved through source triangulation. The results indicate that the implementation of PAI in the Student Festival successfully integrates Islamic values ​​with the dimensions of the Pancasila Student Profile. Through various activities such as Islamic speech competitions, Quran recitations, calligraphy, Islamic drama, and religious quizzes, students not only hone their academic and non-academic skills but also cultivate the practice of religious teachings in real life. The Student Festival has proven to be an effective platform for strengthening students' faith, morals, creativity, cooperation, and independence. Therefore, it can be concluded that the implementation of Islamic Religious Education (PAI) through the Student Festival at MTs Darul Ulum Pasuruan has contributed significantly to strengthening the Pancasila Student Profile. This demonstrates that the integration of religious values ​​and character education can produce students who are globally competitive and grounded in religious values. Abstrak Penelitian ini bertujuan untuk mendeskripsikan implementasi Pendidikan Agama Islam (PAI) dalam penguatan Profil Pelajar Pancasila melalui kegiatan Student Festival di MTs Darul Ulum Pasuruan. Latar belakang penelitian ini berangkat dari pentingnya peran PAI dalam membentuk karakter peserta didik yang tidak hanya cerdas secara intelektual, tetapi juga beriman, bertakwa, dan berakhlak mulia. Sejalan dengan kebijakan pendidikan nasional, Profil Pelajar Pancasila menjadi pedoman dalam menumbuhkan generasi yang religius, kreatif, mandiri, kritis, bergotong royong, serta mampu menghargai keberagaman. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Subjek penelitian terdiri dari kepala madrasah, guru PAI, panitia kegiatan, serta peserta didik. Analisis data dilakukan dengan model interaktif Miles dan Huberman, sedangkan keabsahan data diperoleh melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa implementasi PAI dalam Student Festival mampu mengintegrasikan nilai-nilai keislaman dengan dimensi Profil Pelajar Pancasila. Melalui berbagai kegiatan seperti lomba pidato Islami, tilawah Al-Qur’an, kaligrafi, drama Islami, dan cerdas cermat keagamaan, peserta didik tidak hanya mengasah keterampilan akademik dan non-akademik, tetapi juga membiasakan diri mengamalkan ajaran agama dalam kehidupan nyata. Student Festival terbukti menjadi wadah efektif untuk memperkuat iman, akhlak, kreativitas, kerja sama, serta kemandirian siswa. Dengan demikian, dapat disimpulkan bahwa implementasi PAI melalui Student Festival di MTs Darul Ulum Pasuruan berkontribusi signifikan dalam penguatan Profil Pelajar Pancasila. Hal ini menunjukkan bahwa integrasi antara nilai-nilai agama dan pendidikan karakter mampu mencetak peserta didik yang berdaya saing global sekaligus berlandaskan nilai-nilai religius.